ANALISIS DAN INTERVENSI ERGONOMI PADA INDUSTRI ROTAN DI KABUPATEN CIREBON - Al - Yusni, Mukhammad
Rattan crafts are the largest leading commodity in Cirebon Regency. The manufacturing process are made manually using human labor. Manual work generally has ergonomic risks, one of which is work-related musculoskeletal disorders (WRMSDs). An initial study on rattan business units in Cirebon Regency showed that 6 out of 10 workers experienced WRMSDs complaints with high risks in the hands, arms, shoulders, and lower back. In addition, work stations in rattan craft production were also considered less ergonomic. This study aims to evaluate ergonomics, identify factors that influence WRMSDs, and conduct ergonomic interventions. The jobs observed include cutting, steaming, tying, framing, and decorating. The methods used for the WRMSDs survey and ergonomic evaluation include the WRMSDs questionnaire and a checklist of potential ergonomic hazards based on SNI 9011:2021. Statistical analysis with the chi-square test was used to identify factors that influence WRMSDs. The results of the WRMSDs questionnaire from 100 workers showed a percentage of high-risk complaints in several body parts, namely the neck (22%), elbows (18%), arms (34%), hands (63%), thighs (9%), calves (18%), shoulders (51%), upper back (22%), lower back (66%), hips (15%), knees (17%), and feet (30%). After the WRMSDs survey, an ergonomic evaluation with SNI 9011:2021 was carried out on rattan work with scores for cutting (16), steam (19.5), frame (13), tie (13), and decoration (15). This score indicates that all jobs require improvement. Further analysis includes observations of WRMSDs factors such as gender, age, body mass index (BMI), length of service, smoking status, physical activity, and workstation. The results of the chi-square test showed that only gender, smoking status, and workstation factors had a significant relationship with WRMSDs risk. Ergonomic interventions were carried out by applying the principles of work design and anthropometry as well as administrative control.